A Visit to London for Thomas the Tank Engine - Ronne Randall (UK Egmont Books, 2016)
Join Thomas the Tank Engine on a royal adventure as he attends the Queen's birthday celebrations. The Fat Controller has been invited to the Queen's birthday party, far from the Island of Sodor, in the biggest city in the land, London. And what better engine to take him there than Thomas the Tank Engine. A delighted Thomas makes the long journey to London where he is put on a barge and taken down the Thames seeing Tower Bridge, St Paul's, The Shard, Parliament and many other landmarks along the way. Toddlers will delight in discovering the delights of London with their favourite engine. It's a very proud day for the little blue engine in the big city and a perfect accompaniment to the Queens' 90th birthday celebrations. Great for toddlers aged 2 and up. Thomas has been teaching children lessons about life and friendship for over 70 years. He ranks alongside other beloved character such as Paddington Bear, Winnie-the-Pooh and Peter Rabbit as an essential part of our literary heritage.
Keywords: EY - RM -- EY - RM